Epidemiological analysis of hospitalizations for headache in women at menacme in Brazil, between 2019 and 2023 - Cavagnoli, Giovanna Lourenço; Mendes, Natalia Camila Correia; Queiroz, Bruno Dias; Espindola, Vitor Dias; Messias, Emely Regina; Souza, Marcelo Alves de (Headache Medicine, 2024)
Introduction: Headache is considered the second most frequent type of pain worldwide, generating high costs for patients and health services as a whole. According to the Brazilian Academy of Neurology, women are more likely to develop headache compared to men, a reason attributed to hormonal cycles. Objectives: To describe the number of hospitalizations due to headaches in women at menacme in Brazil between 2019 and 2023. Method: This is a descriptive cross-sectional study, using data collection from the SUS Hospital Information System (SIH/SUS), linked to the Department of Informatics of the Unified Health System (DATASUS) in may 2024. The numbers of hospital admissions for migraine and other cephalic pain syndromes in women at menacme in the 2019-2023 period were analyzed. The variables used were: Age group, gender, year of hospitalization, race/color, average value of hospitalizations, and federation unit/region. Results: During this period, 22,649 hospitalizations for headaches were recorded in women at menacme. Of this total, the Southeast region concentrated the highest number of hospitalizations (32.3%, 7,333), and the state of São Paulo accounted for 61.9% of the cases. The year 2019 had the highest number of records (5,333), followed by 2023, with 4,975 cases. It was observed that headaches predominated in brown races/skin color in the North, Northeast and Midwest regions, which corresponded to 43% of the cases in Brazil. The predominant age group was 30-39 years (28.7%, 6,504). The South region had the highest average hospitalization value (465.72 reais). Conclusion: In view of the analysis, there was a drop in hospitalizations from 2019 onwards, with a new increase in 2023. It was observed that the highest epidemiological profile is related to the Southeast region, especially the state of São Paulo, with brown skin color and age group between 30 and 39 years. The South region was responsible for the highest average number of hospitalizations. Therefore, this conclusion will be valid for the creation of public policies aimed at the prevention and treatment of headache in women at menacme.